Gestão da inovação para a sustentabilidade ambiental: estudos de caso do desenvolvimento e difusão de produtos de consumo industrializados com materiais de fontes renováveis - Calia, Rogério Cerávolo (2010)
The objective of this thesis is to identify how the innovation management of environmentally sustainable product occurs. Utilizing the case study research method and the perspective of three trajectories of the organizational theory (industry structure, resource based view and relational view), it was conducted a broad analysis of how the external conditioners of the ompetitive environment, the internal conditioners in the company and the organizational relationships impacted the development and diffusion project of two product innovations with attributes favorable to the environmental sustainability: a bath sponge with Amazonian fibers and recycled PET and a ready to use dish washing liquid of renewable sources. Both cases presented clear differences in relation to the companies’ size, organizational structure, competences and culture, the maturity of their renewable sources technological platform and the approach utilized in the new product development project management. Moreover, the two cases are different in the functional and environmental product attributes competitiveness related to price and concurrent products. Despite those differences, constructs from the relational view were utilized to identify innovation management similarities in the two cases. Internal informal networks conducted an organizational innovation by creating a sustainability department, which diagnosed and recommended actions, in order to minimize the regulatory, social and environmental risks derived from the supply of the Amazonian fiber for the bath sponge. And a collaborative relationship complemented the product innovation and created marketing innovations that resulted in the best diffusion performance of the dish washing of renewable sources in the retail market. Therefore, despite the differences in the internal and external conditioners, the innovation management in both cases conducted collaborative relationships, in order to generate organizational and marketing innovations that solved the constraints to the process of environmentally sustainable product innovation.